Utilization of Aspergillus niger with Sengon Powder for Integrated IoT-Based Microplastic Biodegradation in Rivers - Syifa Annisa; Nabila Febriyana Najwa; Muhammad Akbar Rabbani; Okti Herawati (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
The increase in microplastic pollution has become a serious threat to ecosystems and human health. Data shoes that approximately 98% of river in Indonesia have been contaminated with microplastics. One biodegradation approach is the use of Aspergillus niger (A. niger), which is able to decompose complex organic polymers into simple compounds through depolymerization and mineralization processes into CO₂, H₂O, or CH₄. Degradation efficiency can be increased by adding sengon powder (Paraserianthes falcataria) as a bulking agent to regulate porosity, humidity, and provide nutrients for fungal growth. This study aims to evaluate the combination of A. niger and sengon powder in decomposing microplastics and develop a microcontroller and IoT-based detection system. Monitoring of microplastic levels can be done through turbidity sensors and optical particle counters connected to the monitoring system. Thus, treatment interventions can be carried out in a timely manner to maintain river quality. This approach is expected to be an environmentally friendly solution to address microplastic pollution effectively and sustainably.